2020
DOI: 10.3390/ijerph17041126
|View full text |Cite
|
Sign up to set email alerts
|

Who Can Help Us on This Journey? African American Woman with Breast Cancer: Living in a City with Extreme Health Disparities

Abstract: This qualitative descriptive research study looks at the services that community-based breast cancer support agencies provide to underserved and African American women who are at risk for or diagnosed with breast cancer in Memphis, Tennessee. We seek their understanding of breast cancer mortality disparities in Memphis. Data were collected using semi-structured in-depth focus groups with five breast cancer support agencies. Categories and patterns were established using thematic analysis and a deductive a prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Sustainable community outreach activities, such as mobile mammography, have proven to help reduce these structural barriers for Black women while offering a possible solution to bolstering breast cancer screening in underserved communities residing in urban and rural settings (Faguy, 2020). Community-based breast cancer support agencies that include patient navigators, breast cancer support groups, and early detection programs also play a pivotal role in maximizing breast cancer outcomes in Black women (White-Means et al., 2020). Other barriers such as having inadequate childcare and having to pay for childcare have been associated with a lack of breast cancer screening (Balas et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sustainable community outreach activities, such as mobile mammography, have proven to help reduce these structural barriers for Black women while offering a possible solution to bolstering breast cancer screening in underserved communities residing in urban and rural settings (Faguy, 2020). Community-based breast cancer support agencies that include patient navigators, breast cancer support groups, and early detection programs also play a pivotal role in maximizing breast cancer outcomes in Black women (White-Means et al., 2020). Other barriers such as having inadequate childcare and having to pay for childcare have been associated with a lack of breast cancer screening (Balas et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…With these financial challenges faced by these women, they had to rely on family members, employers and other people for assistance to enable them go through treatment. A lot of studies have reported similar findings (Sanuade et al, 2018;Twahir et al, 2019;White-Means, Dapremont, Davis, & Thompson, 2020). Amid the financial difficulties, some employers promised to assist some participants with payment of hospital bills;…”
Section: Discussionmentioning
confidence: 85%
“…However, patients were not always made aware of resources (eg, financial services) available to them in a timely manner, if at all. Patient navigators, shown to be valuable to cancer care outcomes, 11,32–34 were endorsed by patients in our study and represent a requirement of OCM practices to ensure patients receive the services they need. Roche et al 10 offered a sample care team map, as an initial step, to delineate resources within a system as one way to alert patients to resources available to them.…”
Section: Discussionmentioning
confidence: 96%
“…Peer groups offered useful information and social support, shared experiences with navigating life with breast cancer and provided a means of networking. Peer social support has been shown to decrease depression, promote psychosocial well‐being and sense of community, and foster exchange of information/experiences 34–37 …”
Section: Discussionmentioning
confidence: 99%